Monitoring Compliance in Patients with Hyperlipidemia Using New Electronic Compliance Recorder - Tsuji, Daiki; Arakawa, Masayuki; Suzuki, Chieko; Ohashi, Kyoichi; Yamada, Hiroshi; Nishio, Shinichiro; Matsumoto, Yoichi; Nakashima, Mitsuyoshi (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2005)
Several methods have been used for achieving good medication compliance-among them one-dose packages, self reporting diaries, and measurement of drug serum concentrations-but such methods are all insufficient for clinical purposes. The aim of this study was to assess the usefulness of a newly developed electronic device for medication compliance (compliance recorder) through the monitoring of daily compliance in patients with hyperlipidemia. Eight patients (mean age : 64 years old, range 57 to 73) taking pravastatin (10 mg/once a day) were randomly assigned to 2 groups-an intervention group for which the electronic compliance recorder was used to evaluate compliance data and a control group not using the recorder. Both groups were checked for total cholesterol and LDL-cholesterol levels on each day hospital visit day, and thereafter compliance was checked through self reporting at the community pharmacy. All data were retrieved from the electronic compliance recorders in the observation periods, the mean of which was 180 days (range 168 to 196 days). The compliance rate calculated for the intervention group was 96.5 % (718 patients days). For the total cholesterol and LDL-cholesterol levels, there were no statistically significant differences between the two groups in the observation periods. From the self-reporting scores, the intervention group maintained good compliance throughout the observation periods. These results suggest that the electronic compliance recorder is a useful tool for improving compliance.